Sistematización de la participación política y social de los miembros de la Comunidad San Francisco de Cajas, provincia de Pichincha e Imbabura en los últimos cinco años. - Inlago Andrango, Martha Yolanda (2016)
This research is a systematization of experiences of the political and social participation in the community of San Francisco de Cajas, in order to know the strengths and weaknesses inside the community. The main objective is to assess the political and social participation of community members over the past five years. The research method applied in this systematization, is to look at one or more experiences, to make a critical interpretation of those experiences; that, from its planning and reconstruction, discover and explain the logic of the living process where several factors interrelated are involved. One of the most important findings of the research is that there is an association between electoral participation and access to public services with political participation only, while social and community participation is considered as everyday practices in favor of their community. Also, it was evident a decline of historical memory and lack of community leadership due to migration and changing of economic and productive activities. In addition, identity and cultural changes are a transverse axis to understand the decline of political participation in the studied community. The continued participation and leadership of women is also evidence. Finally, this work facilitated the development of skills of planning and implementing social and policies activities within the community, as well as the development of skills to initiate links with other communities or strengthen old ones, promoting the exchange of knowledge, and to the development of the Annual Plan of Activities.